Growth hormone treatment in congenital tufting enteropathy: a case report and literature review - Oktay, Mehmet Ali; Çamurdan, Mahmut Orhun; Gürkan, Ödül Eğritaş; Tehçi, Başak Alan; Döğer, Esra; Bideci, Aysun (Frontiers in Endocrinology, 2025)
This article aims to evaluate the effects of growth hormone (GH) therapy in a case with congenital tufting enteropathy (CTE). CTE is a rare autosomal recessive enteropathy that typically presents with persistent diarrhea. In this case, a 13-year-old girl presented with a diagnosis of CTE. Due to short stature, GH therapy was considered. Pre- and post-treatment evaluations were conducted for height, growth rate, and motor skills. As a result, an increase in growth rate and improvement in motor skills were observed with GH therapy. These findings suggest that the potential of GH therapy is to increase growth and improve the quality of life in patients with CTE. Further studies are needed to evaluate the long-term effects of GH therapy and its efficacy in broader patient groups.